Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Comparison of direct oral anticoagulants to vitamin-K antagonists as treatment for leaflet thrombosis after Transcatheter Aortic Valve Implantation (TAVI) - Ferstl, Paul; Marwan, Mohamed; Achenbach, Stephan; Bittner, Daniel (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Comparison of oral anticoagulation by vitamin-K antagonists and non-vitamin-K antagonists for treatment of leaflet thickening after transcatheter aortic valve implantation (TAVI) - Ferstl, Paul; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (International Journal of Cardiology, 2023)
Introduction: Hypoattenuated leaflet thickening (HALT), as identified by CT imaging, is not infrequent after transcatheter aortic valve implantation (TAVI). The best choice of oral anticoagulation is unknown. We compared the effectiveness of Direct Oral AntiCoagulants (DOAC) and Vitamin-K Antagonists (VKA) to resolve HALT in patients with serial CT aquisitions. Methods: A total of 46 consecutive TAVI patients in whom anticoagulation had been initiated because of HALT and who underwent follow-up CT were identified. Indication and type of anticoagulation was according to physician discretion. Patients on DOAC were compared to VKA therapy regarding resolution of HALT. Results: Mean age of the 46 patients was 80 ± 6 years (59% men), and the mean duration of anticoagulation was 156 days. Overall, 41 patients (89%) showed resolution of HALT with anticoagulation therapy, whereas HALT persisted in 5 patients (11%). Resolution of HALT was seen in 26 out of 30 (87%) patients receiving VKA and in 15 out of 16 (94%) patients receiving DOAC, respectively. Groups did not differ regarding age, cardiovascular risk factors, TAVI prosthesis type and size or duration of anticoagulation (all p > 0.05). Conclusion: Anticoagulation therapy resolves leaflet thickening after TAVI in most patients. Non-Vitamin-K antagonists seem to be an effective alternative to Vitamin-K antagonists. This finding needs to be confirmed in larger prospective trials.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Anticoagulation; HALT; Leaflet thickening; TAVI

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Influence of lesion location on the accuracy of CT derived FFR: head-to-head comparison with invasive FFR - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan; Ammon, Fabian; Ferstl, Paul; Göller, Markus; Bittner, Daniel O.; Uehlein, Sabrina; Bal, Zeynep; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Resolution of leaflet thrombosis under anticoagulant therapy in patients after transcatheter aortic valve implantation: influence of prosthesis type and size - Ferstl, Paul; Arnold, Martin; Göller, Markus; Ammon, Fabian; Smolka, S.; Moshage, Maximilian; Uehlein, Sabrina; Achenbach, Stephan; Bittner, Daniel O.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial